International anarchy? Modern adoption of Hobbes’s state of nature - Monthathip, Krishna (Frontiers in Political Science, 2025)
Contemporary International Relations (IR) scholars tend to understand Hobbes’s conceptions of the state of nature and sovereign state by imposing modern concepts and categories without paying enough attention to the historical and ideational contexts which shaped Hobbes’s political thought. In doing so, they apply Hobbes’s notion of the state of nature to apprehend international politics and claim that the international realm, from Hobbes’s view, would be a realm of anarchy and, thus, deem that states are justified in conducting power-maximising practices without any moral consideration. Having been inspired by the contributions of a constructivist perspective, which emphasises the importance of historical and ideational contexts surrounding thinkers in the past, I argue that, to apprehend Hobbes’s understanding of relations between states, it is necessary to realise that Hobbes developed the idea of the state of nature in response to Europe’s religious-based violent conflicts, an intellectual debate between the Calvinists and Arminians, and England’s expansion of colonial activities in America. By employing this alternative methodological lens, I argue that we can re-read Hobbes’s understanding of international politics differently from the realist orthodox account mentioned earlier. First, I will address the methodological problems of the realist approach and offer the constructivist perspective and its contributions to understanding Hobbes’s political thought. Second, I then explore a scholarly tradition historicising Hobbes’s political thought. Third, I will examine the crucial historical and intellectual contexts that influenced Hobbes’s notion of the state of nature. Lastly, I will re-read Hobbes’s understanding of relations between states by considering the importance of the principle of the right of self-preservation.